(untitled) (Journal of Engineering, 2016)
Non uniform channelization is a crucial task in cognitive radio receivers for obtaining separate channels from the digitized wideband input signal at different intervals of time. The two main requirements in the channelizer are reconfigurability and low complexity. In this paper, a reconfigurable architecture based on a combination of Improved Coefficient Decimation Method (ICDM) and Coefficient Interpolation Method (CIM) is proposed. The proposed Hybrid Coefficient Decimation-Interpolation Method (HCDIM) based filter bank (FB) is able to realize the same number of channels realized using (ICDM) but with a maximum decimation factor divided by the interpolation factor (L), which leads to less deterioration in stop band attenuation (SA). The proposed architecture is able to realize a greater number of sub-bands locations. The proposed (HCDIM) based (FB) shows an inherent low complexity offered by the (CIM) technique when compared with the alternative FBs. The reduction in the number of multiplications is by 50.77% compared with ICDM in non-uniform channelization, while the reduction in the number of multiplications is about 59.64% over the discrete Fourier transform (DFTFB) and 31.19% over ICDM based FB in uniform channelization.